Usability evaluation on fish auction information system application using system usability scale - Sofiyan Muji Permana; Dewi Susiloningtyas; Sri Suryo Sukoraharjo (Institute of Computer Science (IOCS), 2023)
One of the impacts of technological developments in the fisheries sector is the development of the Integrated Fish Auction Information System (FAIS). The Integrated Fish Auction Application supports the process of managing fisheries data at the port. The purpose of this study is to evaluate the results of usability in integrated fish auction applications. The research method begins with determining the object of research, collecting data, and using the System Usability Scale method as a scenario determination, respondent selection, data collection, and calculation. The test value displays 60.08 which has a sufficient usability value, with acceptability marginal, grade scale value D, and adjective rating criteria ok. The System Usability Scale (SUS) results conclude that usability testing of the Integrated Fish Auction Application is still acceptable to auction participants and runs well.